Social responsibility and engagement in higher education: Case of the ASEAN - Symaco, Lorraine Pe; Tee, Meng Yew (Elsevier, 2019)
This article discusses the role of ASEAN universities in social responsibility and sustainable development. Selected country case studies are presented to describe the changing role of universities situated in a region with great diversity and potential for further economic growth, as we explore the opportunities and challenges in promoting higher education institutions (HEIs) for greater sustainable development of communities. While there is a wide variety of initiatives—including engaging diverse communities in health, education and environmental sustainability projects— social responsibility and sustainability development is still far from being fully integrated into the core activities of the HEIs. This paper will examine the broader capacity of the universities’ engagement in social responsibility, as interpreted within Boyer's framework on the scholarship of engagement. We argue that when HEIs develop an integral socially-responsible collaboration with the broader community, opportunities are created for unique epistemic advances for stakeholders involved. © 2018 Elsevier Ltd